The Effect of Celebrity Endorser and Brand Image on Vivo Smartphone Purchase Decision (Study on the Community of Sukaraja District, Seluma Regency) - Peni Juniarti; Ermy Wijaya; Yesi Indian Ariska (Penerbit Jurnal Indonesia, 2022)
The purpose of this study was to determine whether there is a simultaneous influence of celebrity endorser and brand image on Vivo Smartphone purchasing decisions in the Sukaraja District, Seluma Regency. The sample in this study was 100 people from Sukaraja District, Seluma Regency. The data was collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. From the calculation of the multiple linear regression equation, it can be seen that X1 (celebrity endorser) and X2 (brand image) have an influence on purchasing decisions (Y), with the results of the regression test: Y = 18.497 + 0.187X1 + 0.381 X2 + e. The coefficient of determination of R square is 0.356. This means that celebrity endorser (X1) and brand image (X2) affect the purchasing decision of Vivo Smartphone (Y) by 54.4% while the remaining 45.6% is influenced by other variables not examined in this study. Based on the test results with the t test, the hypothesis made proves that there is an effect. The test results for the X1 variable (celebrity endorser) show a significance value of 0.000 <0.05. Because the significance value is less than 0.05, then X1 (celebrity endorser) has a significant influence on purchasing decisions (Y). Variable X2 (brand image) shows a significance value of 0.000 < 0.05. Because the significance value is less than 0.05, then X2 (brand image) has a significant influence on purchasing decisions (Y). Based on the results of hypothesis testing with the F test, a significance value of 0.000 <0.05 and a significance level below 0.05 indicates that jointly celebrity endorser (X1) and brand image (X2)) have a positive and significant influence on decisions purchase (Y).